JavaScript best practices : getting better at JavaScript syntax, modules, objects, and environments (DOM and Node) - McPeak, Jeremy, 1979-; Safari eBooks ([Place of publication not identified] : O'Reilly, 2017)
"Developers everywhere use JavaScript to build websites and desktop applications. While it's relatively simple to learn JavaScript basics, it can be a difficult language to truly master. This course helps you transition from JavaScript novice to JavaScript pro by teaching you the techniques and practices used by the seasoned practitioner. The only prerequisites are beginning level JavaScript experience, access to a good code editor (like Visual Studio Code), and the desire to improve."--Resource description page.
Presenter, Jeremy McPeak.
Title from title screen (viewed April 6, 2017).
Date of publication from resource description page.
Keywords: JavaScript (Computer program language); Application software -- Development; Electronic books